The House of Sacrifice - Lidin, Konstantin (project baikal, 2014)
The main difference between a temple and any other religious structure is that the former has an altar and a function of offering sacrifices. For thousands of years people have been offering various substances. The simplest sacrifices, like food or possessions, fragments of one’s own body or human lives gave way to more complex and symbolic ones as the civilization evolved. People offered individuality, logic, common sense, lifestyle etc. Architectural features, structure and appearance of a temple are also formed according to characteristics of sacrifices. The temple of the 21st century is featured by sacrificing different kinds of emotions. That is why the temple architecture of the 21st century has such a wide range of diversity.
Keywords: Temple; sacrifice; culture; architecture; history; modern times; prospects